2022
DOI: 10.4081/monaldi.2022.2418
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism and gastric bleed with disseminated mucormycosis - treading dangerous waters

Abstract: Mucormycosis is an opportunistic infection seen in immunocompromised patients or in surgical and trauma settings with Mucorales wound contamination. In immunocompetent people, disseminated mucormycosis is uncommon. To ensure survival, patients with mucormycosis require early diagnosis and aggressive treatment using a multi-modality approach. We present a case of disseminated mucormycosis in an immunocompetent patient who also had pulmonary embolism and gastrointestinal bleeding. A recent severe acute respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 12 Recent articles on COVID-19-associated mucormycosis (CAM) have been published. 3 - 6 , 8 , 9 It is estimated a higher prevalence of CAM than the reported cases because of the lack of population-based research. Thus, CAM cases may be higher than the described ones.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“… 12 Recent articles on COVID-19-associated mucormycosis (CAM) have been published. 3 - 6 , 8 , 9 It is estimated a higher prevalence of CAM than the reported cases because of the lack of population-based research. Thus, CAM cases may be higher than the described ones.…”
mentioning
confidence: 99%
“…Chauhan et al 3 reported a 35-year-old man with fever, vomiting, delirium, dyspnea, and cough, in addition to melena. Pulmonary thromboembolism and bilateral ground glass opacities were revealed by chest imaging study.…”
mentioning
confidence: 99%
See 2 more Smart Citations